Banana Moko disease management with resistance inducers and chlorine dioxide (2015)
The plant disease Moko, caused by Ralstonia solanacearum, is the most important bacterial disease in banana and plantain crops worldwide. In the present study, chlorine dioxide and seven resistance inducers in banana plants (Musa sp.) infected with this bacterium were evaluated under greenhouse conditions. For the evaluation of chlorine dioxide, three doses were used (10, 30 and 50 mg L-1). The evaluation of the resistance inducers included the following: sodium salicylate 0.4 g L-1; hydrogen peroxide 1 mM; potassium phosphite 1.5 mL L-1; 3-aminobutanoic acid 1.0 g L-1; methyl jasmonate 0.2 g L-1; acibenzolar-s-methyl 0.3 mL L-1 and chitosan 3.0 mg mL-1. The results showed a significant reduction of 74% in the area under the disease progress curve (AUDPC) value, which was calculated for the disease development when the injected chlorine dioxide dose was 50 mg L-1. The AUDPC value for the resistance inducers was reduced by 45.4% for chitosan, 75.5% for methyl jasmonate and 65.5% for 3-aminobutanoic acid. Therefore, the results indicated that these molecules have the potential to be used for control of the Moko disease.